Comparative Analysis of Ibn-Arabi and Molavi's Mystical Language Characteristics - Ghodratollah Khayatian; Tannaz Rashidinasab (مطالعات زبانی و بلاغی)
Mystics and Sufis have composed volumes in prose and poetry, in state of revelations and spirits, education and nurture, and biography. These volumes are of rhetorical and literary value; the vest of these works and special characteristics of the language they had, have caused, putting them in the circle of researcher's attention as the mystical language. It is crystal clear that Ibn-Arabi and Molavi are of the greatest mystic in the Sufism world. The effect of their thoughts and the lingual characteristics in the volumes they have composed was so strong that we can consider the works of the mystics of the other centuries just some simple interpretation and analysis of their thoughts. This study is an effort to comparative and contrastive understanding of the mystical language of these too well-known mystics that indeed can reach the characteristics of the mystical language of each one of them. In the investigation of their works, there are similarities and differences.